Comportamiento Epizootiológico de Parásitos (gastrointestinales) en Caninos Domésticos (canis familiaris) en el Barrio Salache Norte de la Parroquia Eloy Alfaro - Guanoluisa Llamba, Erik Estuardo (2018)
The present investigation is based on the epizootiological behavior of parasites (gastrointestinal) in domestic canines (canis familiaris). Gastrointestinal parasites occur frequently in the canine population, posing a risk to pets and their owners. Since the people who live with canines are susceptible to suffer parasitism. This research was conducted in the northern Salache neighborhood of the Eloy Alfaro parish with the objective of determining the epizootiological behavior of gastrointestinal parasites in domestic canines (canis familiaris) by coproparasitic flotation analysis with sucrose solution (sheather technique). Place the samples in the mixing containers and strain them, allowing them to settle for later observation under a microscope. Of the 150 samples analyzed in the laboratory, 89 cases were positive for parasitosis, representing 59.3% and 61 negative cases representing 40.6% of positive cases, 10.65% for hookworm, and 3.33 ascaris %, toxocara 10% and ancylostoma 27.77%. The positive cases found in canines from 0-12 months are 13 patients representing 100%, of which 5 patients present Ancylostoma caninum representing 77%, presented a canine with Ascaris that corresponds to 0.6%, 3 canines with 2% of Toxocara and 4 animals with 2.6% of Uncinaria. In positive cases in canines from 1 to 5 years, 29 cases were represented, representing 100%, 64 positive for Ancylostoma caninum with 78%, 4 positive for Ascaris representing 15%, 12 positive for Toxocara canis, which is 6% and 7 positive cases to uncinaria that represents 3%. In dogs older than 5 years, 17 positives representing 100%, 75% of Ancylostoma caninum with 17 positives, for Ascaris a positive with 25%. In the sex variable of the canines there were 40 positive cases for males, 20 cases of Ancylostoma caninum, which represents 78%, 3 positive for Ascaris 19%, 10 positive for Toxocara canis with 2% and 7 positive for uncinaria correspond 4.7%. In females the positive ones for parasites were 29 patients for Ancylostoma caninum, 21 positive that is 76%, of Ascaris 5 positive 13%, 8 of Toxocara canis with 9% and 9 presented Uncinaria with 6%. For the race variable, 3 positives were found for the French Poodle breed, one case for Ancylostoma caninum with 50% and one for Uncinaria with 50%. For the mestizo breed 84 positive, 40 cases for Ancylostoma caninum which is 78%, 5 positive for Ascaris 15%, 17 positive for Toxocara canis with 5% and 15 positive for Uncinaria that corresponds to 6%, evidencing that Nematode parasites are the ones that have the highest prevalence in the Barrio Salache Norte; therefore, it is necessary to implement health education actions to the community and the elaboration of deworming plans for the pets.